The Brain as the Original Accounting Institution - Dickhaut, John (The Accounting Review, 2009)
ABSTRACT: The evolved brain neuronally processed information on human interaction long before the development of formal accounting institutions. Could the neuronal processes represent the underpinnings of the accounting principles that exist today? This question is pursued several ways: first as an examination of parallel structures that exist between the brain and accounting principles, second as an explanation of why such parallels might exist, and third as an explicit description of a paradigm that shows how the benefits of an accounting procedure can emerge in an experiment.